Análisis Cinemático y Dinámico de un Robot Paralelo Espacial RUS - Cuenca Jiménez, Francisco (My University, 2008)
Análisis Cinemático y Dinámico de un Robot Paralelo Espacial RUS
Keywords: Análisis Cinemático y Dinámico de un Robot Paralelo Espacial RUS